Lactobacilli Attenuate the Effect of Aggregatibacter actinomycetemcomitans Infection in Gingival Epithelial Cells - Bueno, Manuela R.; Ishikawa, Karin H.; Almeida-Santos, Gislane; Ando-Suguimoto, Ellen S.; Shimabukuro, Natali; Kawamoto, Dione; Mayer, Marcia P. A. (Frontiers in Microbiology, 2022)
The mechanisms underlying the use of probiotics in the prevention or control of periodontitis are still not fully elucidated. This in vitro study aimed to evaluate the effect of two commercially available strains of lactobacilli on gingival epithelial cells (GECs) challenged by Aggregatibacter actinomycetemcomitans. OBA-9 GECs were infected with A. actinomycetemcomitans strain JP2 at a MOI 1:100, and/or co-infected with Lactobacillus acidophilus La5 (La5) or Lacticaseibacillus rhamnosus Lr32 (Lr32) at a MOI 1:10 for 2 and 24 hours. The number of adherent/internalized bacteria to GECs was determined by qPCR. Production of inflammatory mediators (CXCL-8, IL-1β, GM-CSF, IL-10) by GECs was determined by ELISA, and expression of genes encoding cell receptors and involved in apoptosis was determined by RT-qPCR. Apoptosis was also analyzed by Annexin V staining. There was a loss in OBA-9 cells viability after infection with A. actinomycetemcomitans or the tested probiotics after 2 hours which was magnified after 24h co-infection. Adherence of A. actinomycetemcomitans to GECs was 1.8x107 (± 1.2x106) cells/well in the mono-infection, but reduced to 1.2x107 (± 1.5x106) in co-infection with Lr32, and to 6x106 (± 1x106) in the co-infection with La5 (p<0.05). GECs mono-infected with A. actinomycetemcomitans produced CXCL-8, GM-CSF and IL-1β, and co-infection with both probiotic altered this profile. While co-infection of A. actinomycetemcomitans with La5 resulted in reduced levels of all mediators, co-infection with Lr32 reduced levels of CXCL-8 and GM-CSF but increased IL-1β. The probiotics up-regulated expression of TLR2, and down- regulated TLR4, in cells co-infected with A. actinomycetemcomitans. A. actinomycetemcomitans-induced upregulation of NRLP3 was attenuated by La5 but increased by Lr32. Furthermore, the transcription of the antiapoptotic gene BCL-2 was upregulated whereas the pro-apoptotic BAX was down-regulated in cells co-infected with A. actinomycetemcomitans and the probiotics. Infection with A. actinomycetemcomitans induced apoptosis in GECs whereas co-infection with lactobacilli attenuated the apoptotic phenotype. Both tested lactobacilli may interfere in A. actinomycetemcomitans colonization of the oral cavity by reducing its ability to interact with gingival epithelial cells and modulating cells response. However, L. acidophilus La5 properties suggest that this strain has a higher potential to control A. actinomycetemcomitans-associated periodontitis than L. rhamnosus Lr32.